Immunogenicity of modified vaccinia virus Ankara expressing the hemagglutinin stalk domain of pandemic (H1N1) 2009 influenza virus. (17th February 2017) - Di Mario, Giuseppina; Soprana, Elisa; Gubinelli, Francesco; Panigada, Maddalena; Facchini, Marzia; Fabiani, Concetta; Garulli, Bruno; Basileo, Michela; Cassone, Antonio; Siccardi, Antonio; Donatelli, Isabella; Castrucci, Maria R.
Abstract: Background: Vaccination offers protection against influenza, although current vaccines need to be reformulated each year. The development of a broadly protective influenza vaccine would guarantee the induction of heterosubtypic immunity also against emerging influenza viruses of a novel subtype. Vaccine candidates based on the stalk region of the hemagglutinin (HA) have the potential to induce broad and persistent protection against diverse influenza A viruses. Methods: Modified vaccinia virus Ankara (MVA) expressing a headless HA (hlHA) of A/California/4/09 (CA/09) virus was used as a vaccine to immunize C57BL/6 mice. Specific antibody and cell-mediated immune responses were determined, and challenge experiments were performed by infecting vaccinated mice with CA/09 virus. Results : Immunization of mice with CA/09-derived hlHA, vectored by MVA, was able to elicit influenza-specific broad cross-reactive antibodies and cell-mediated immune responses, but failed to induce neutralizing antibodies and did not protect mice against virus challenge. Conclusion : Although highly immunogenic, our vaccine was unable to induce a protective immunity against influenza. A misfolded and unstable conformation of the hlHA molecule may have affected its capacity of inducing neutralizing antiviral, conformational antibodies. Design of stable hlHA-based immunogens and their delivery by recombinant MVA-based vectors has the potential of improving this promising approach for a universal influenza vaccine.